Association Between Accommodative Amplitudes and Amblyopia. (June 2013) - Singman, Eric; Matta, Noelle; Tian, Jing; Silbert, David
Abstract Purpose: To evaluate the relationship between amblyopia and accommodative ability. Methods: The open-field Grand Seiko binocular autorefractor has become the gold standard for automated measurement of static accommodation. We measured the accommodation amplitudes in 52 children ages 3 to 14 years employing the Grand Seiko auto refractor. Children wore their glasses for this test, which was prescribed based on a cycloplegic refraction performed by one pediatric ophthalmologist. No readings could be obtained for 9 eyes (5 patients). Results: Normal accommodation with correction utilizing full accommodative effort at 1/3 meter is 3D assuming no accommodative lag, and would generate a reading of −3.00D from the Grand Seiko auto refractor. Lack of any accommodative should give a reading of 0.00D. Accommodative gradually declined as the acuity worsened. Conclusion: Our results suggest that amblyopic eyes do not accommodate as well as non-amblyopic eyes. Because accommodation amplitude is not subjective it may be a more sensitive indicator of regression of amblyopia than visual acuity. The Grand Seiko autorefractor could prove to be a useful tool to monitor the progress of patients with amblyopia.